SPE Annual Technical Conference and Exhibition 2011
DOI: 10.2118/147410-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Low Salinity Waterflooding for 26 Fields in Wyoming

Abstract: This report evaluates the effectiveness of low-salinity waterflooding in the Minnelusa Formation in the Powder River Basin of Wyoming. The Minnelusa sandstone play constitutes a resource of over one-hundred fields with cumulative production of more than 600,000,000 barrels of oil. We conducted initial laboratory screening using Minnelusa oil and rock with synthetic brine, supplemented with geochemical models of low-salinity injection, to evaluate the potential for low-salinity waterflooding in this formation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Although fines migration is no longer thought to be a major mechanism for LSW wettability alteration [16 • ,38,24,5], it may be important in certain cases. In a few laboratory experiments, LSE is observed only in cores where there is fines migration [25,40]. It is unclear why in these studies, DLE and the chemical mechanisms do not improve the oil recovery unless fines are also produced.…”
Section: Limitations Of Dle and The Chemical Mechanismsmentioning
confidence: 97%
“…Although fines migration is no longer thought to be a major mechanism for LSW wettability alteration [16 • ,38,24,5], it may be important in certain cases. In a few laboratory experiments, LSE is observed only in cores where there is fines migration [25,40]. It is unclear why in these studies, DLE and the chemical mechanisms do not improve the oil recovery unless fines are also produced.…”
Section: Limitations Of Dle and The Chemical Mechanismsmentioning
confidence: 97%
“…Other than using high salinity reservoir water, extensive laboratory experiments ( Thyne and Gamage, 2011) have confirmed the advantages of using low salinity brine as an injected fluid on the oil recovery for both secondary and tertiary modes. LSW has received increasing attention in the oil industry and is currently indentified as an important EOR technique as it shows more advantages than conventional chemical EOR methods in terms of chemical costs, environmental impact, and field process implementation.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the oil recovery trend in historical data appeared to increase as the salinity ratios decreased, which corroborated laboratory corefloods using Berea outcrop material. Similarly, from a large dataset of waterflooding in Wyoming fields available in public records, Thyne et al [221] published a comprehensive evaluation of historical low saline brine injection in 26 fields and compared with laboratory corefloods. In contrast to Robertson [220], they found no correlation between dilution and oil recovery.…”
Section: Sandstone Reservoirsmentioning
confidence: 99%